Assessment on tight oil resources in major basins in China. (July 2019) - Guo, Qiulin; Wang, Shejiao; Chen, Xiaoming
Highlights: Resource-Richness Analogy Approach used in less explored reservoirs is proposed. Genesis-Statistics Assessment Approach for heterogeneous tight oil is proposed. The parameter criteria of lacustrine tight oil resource assessment are established. In-place tight oil resources in China's major basins are estimated of 12.6 × 10 9  t. 15 most favorable plays are outlined with in-place resources of 5.3 × 10 9  t. Abstract: Large-scale commercial development of shale gas and tight oil resources in North American and continuous discoveries of tight oil in China lead to the recognition of the importance of assessment on tight oil resources. Based on the characteristics of China's tight oil reservoirs and exploration status, this paper discusses a workflow focusing on in-place resource evaluation. In the workflow, a Resource-Richness Analogy Approach (RR-AA) is proposed for assessment of tight oil resources in less explored areas, a Genesis-Statistics Assessment Approach (GS-AA) for lacustrine tight oil resources with strong heterogeneity and regions where more delicate assessment is required, and an EUR Analogy Approach (EUR-AA) for assessment on recoverable tight oil by fully using available EUR data of production wells. After analyzing the geological characteristics of the formation of tight oil in the Ordos, Bohai Bay, Songliao, Junggar, Sichuan and other major Basins, the distributions of essential parameters such as reservoir thickness, area and porosity have been defined, and the parameter evaluation criteria have been established. Finally, the tight oil resource potentials in the major basins in China have been evaluated using one of the three methods and the prospective areas of high resource abundance are outlined in each of basins. The results from this study show that China's tight oil resources have a large potential and good exploration future. The estimated in-place tight oil resources are 12.580 × 10 9 tons, mainly distributed in the Ordos, Songliao, Bohai Bay and Junggar Basins. 15 most favorable zones are proposed having in-place resources of 5.296 × 10 9 tons.